Optimizing the use of topical retinoids in Asian acne patients. Issue 5 (3rd April 2018) - See, Jo‐Ann; Goh, Chee Leok; Hayashi, Nobukazu; Suh, Dae Hun; Casintahan, Flordeliz Abad
Abstract: Acne vulgaris is a common disease among people in Asia. International guidelines and treatment recommendations emphasize the central role of topical retinoids in the management of acne. However, topical retinoids remain underutilized in clinical practise, which may be in part due to fear of retinoid‐associated dermatitis/lack of experience, particularly in Asian patients. There is a perception that Asian skin has a greater tendency toward sensitivity compared with Caucasian skin. In our clinical experience, topical retinoid therapy can be used with excellent effect to treat Asians with acne. This article discusses available published work regarding the use of topical retinoids in Asian populations, and presents tips for utilizing these important agents in daily practise. Optimizing use of topical retinoids may improve adherence and, in turn, therapeutic outcomes and patient satisfaction.